Evaluation of the rapid weight loss practices of taekwondo athletes and their effects - Seyhan, S. (Journal of Education and Training Studies, 2018)
This study was conducted to determine the physiological and psychological effects of the weight loss by determining the weight loss methods commonly used by taekwondo athletes. Of the questionnaires evaluated, 107 belonged to female taekwondo athletes and 195 belonged to male taekwondo athletes. The arithmetic average, standard deviation and percent frequency (%) distributions of the obtained data were calculated. It was determined that the; first weight loss age for the competition is 15,66±3,84 (kg) in males and 15,95±3,16 (kg) in females; the highest weight loss rate before the competition is 4,52±2,77 (kg) in males and 4,40±5,36 (kg) in females. It was stated that 30.3% of male athletes and 41.1% of female athletes start to lose weight 3-4 weeks before the competition, that male and female athletes prefer the diet method most frequently as a rapid weight loss method and 21.5% of athletes who use the weight loss method with fluid loss prefer to run with raincoat. The athletes do not use ergogenic aids and the frequency percentage of physiological (muscle cramps, body temperature increase, heart throb, dyspnea, injury) and psychological (excessive nervousness, low performance due to high fatigue, stress) adverse effects of fast weight loss is very low.